AMÉRICA LATINA COMO EXPRESIÓN DEL SISTEMA-MUNDO EN LA ORGANIZACIÓN DE LOS MODELOS DE DESARROLLO - Martins, Paulo Henrique (Caderno CRH, 2013)
Nuestra idea es que la definición de América Latina como manifestación particular del sistema mundo es importante para aclarar el entendimiento de las innovaciones teóricas, sociales, culturales, tecnológicas, estéticas e institucionales verificadas en la región desde el final de la segunda guerra mundial. Sin embargo, el carácter de esta definición depende directamente de un entendimiento anterior respecto a lo que significa el sistema mundo y el desarrollo. Porque si definimos el sistema mundo como una unidad homogénea no tiene sentido hablar de manifestaciones particulares de este sistema; por otro lado, si limitamos el sistema mundo al sistema capitalista, la idea de particularidad de América Latina también queda complicada cuando pensamos la región como base de procesos políticos y culturales liberatorios y propios. En fin, recordamos que este análisis se inspira en contribuciones inestimables de la Comisión Económica para América Latina y Caribe – CEPAL – que ha planteado de modo pionero innovaciones importantes sobre el tema del desarrollo, contribuyendo con la ruptura del ideario colonial. PALABRAS-CLAVES: América Latina. Sistema-Mundo. Desarrollo. LATIN AMERICA AS AN EXPRESSION OF WORLD-SYSTEM IN THE ORGANIZATION OF DEVELOPMENT MODELS Paulo Henrique Martins Our idea is that the definition of Latin America as a particular manifestation of worldsystem is important for clarifying the understanding of innovations that have taken place in the region since the end of World War II, whether they be theoretical, social, cultural, technological esthetic, or institutional. Nevertheless, the character of this definition depends directly on a prior understanding of the meaning of world-system and of development. If we define world-system as a homogeneous unit, it makes no sense to talk about particular manifestations within this system. On the other hand, if we limit world-system to the capitalist system, the idea of Latin America’s particularity becomes complicated when we think of the region as a base for political and cultural processes, both borrowed and original. After all, we must remember that the inspiration for this analysis is the inestimable contributions made by CEPAL (Economic Commission for Latin America and the Caribbean), which pioneered important innovations to the theme of development, thus contributing to a break with the colonial mindset. KEY WORDS: Latin America. World-system. Development. L’AMÉRIQUE LATINE COMME EXPRESSION DU SYSTÈME-MONDE DANS L’ORGANISATION DES MODÈLES DE DÉVELOPPEMENT Paulo Henrique Martins Nous partons de l’idée que la définition de l’Amérique Latine comme manifestation particulière du système-monde est importante pour clarifier la compréhension des innovations théoriques, sociales, culturelles, technologiques, esthétiques et institutionnelles confirmées dans la région depuis la fin de la deuxième guerre mondiale. Cependant le caractère de cette définition dépend directement d’une compréhension préalable mise en rapport avec ce que l’on entend par système-monde et développement. Car si l’on définit le système-monde comme une unité homogène, cela n’a aucun sens de parler de manifestations particulières de ce système, d’autre part, si nous limitons le système-monde au système capitaliste, l’idée de particularité de l’Amérique Latine se complique, elle aussi, si nous pensons à la région comme à une base de processus politiques et culturels libératoires et propres. Enfin, rappelons que cette analyse s’inspire des contributions inestimables de la CEPAL (Commission Économique pour l’Amérique Latine et les Caraïbes) qui, en tant que pionnière, a introduit d’importantes innovations concernant le développement et a apporté une contribution à l’effondrement des idées coloniales. MOTS-CLÉS: Amérique Latine. Système-Monde. Développement. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; font-weight: bold;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; display: inline ! important; float: none; font-weight: bold;"> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; font-weight: bold;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br